Age-related differences in the response of the L5-S1 intervertebral disc to spinal traction. (October 2017) - Mitchell, Ulrike H.; Beattie, Paul F.; Bowden, Jennifer; Larson, Robert; Wang, Haonan
Abstract: Background: Lumbar traction is a common treatment for low back pain; however its mechanisms of action are poorly understood. It has been hypothesized that a key effect of lumbar traction is its capacity to influence fluid movement within the intervertebral disc (IVD). Objectives: To determine differences in the apparent diffusion coefficient (ADC) obtained with lumbar diffusion-weighted imaging (DWI) of the L5-S1 IVD before, and during, the application of lumbar traction. Design: Case series, repeated measures. Methods: A static traction load of ∼50% of body-weight was applied to the low back using a novel "MRI-safe" apparatus. DWI of the lumbar spine was performed prior to, and during the application of the traction load. Results: Participants were currently asymptomatic and included a young adult group (n = 18) and a middle-aged group (n = 15). The young adult group had a non-significant 2.2% increase in ADC (mean change = 0.03 × 10 −3  mm 2 /s, SD = 0.24, 95% CI = −0.09, 0.15). The ADC for the middle-aged group significantly increased by 20% (mean change of 0.18 × 10 −3  mm 2 /s, SD = 0.19; 95% CI = 0.07, 0.28; p = 0.003; effect size = 0.95). There was an inverse relationship between the ADC obtained before traction and the percent increase in ADC that was measured during traction. Conclusion: Static traction was associated with an increase in diffusion of water within the L5-S1 IVDs of middle-age individuals, but not in young adults, suggesting age-related differences in the diffusion response. Further study is needed to assess the relationship between these findings and the symptoms of back pain. Level of evidence: 4. Highlights: Static traction is associated with an increase in ADC in older discs, not younger. Inverse relationship between baseline ADC and percent increase with traction. Findings suggest presence of age-related changes in the rate of diffusion response. Real-time MR imaging while performing traction is possible.